Corticotropin-Releasing Hormone As the Homeostatic Rheostat of Feto-Maternal Symbiosis and Developmental Programming In Utero and Neonatal Life - Alcántara-Alonso, Viridiana; Panetta, Pamela; de Gortari, Patricia; Grammatopoulos, Dimitris K. (Frontiers in Endocrinology, 2017)
A balanced interaction between the homeostatic mechanisms of mother and the developing organism during pregnancy and in early neonatal life is essential in order to ensure optimal fetal development, ability to respond to various external and internal challenges, protection from adverse programming and safeguard maternal care availability after parturition. In the majority of pregnancies this relationship is highly effective resulting in successful outcomes. However, in a number of pathological settings, perturbations of the maternal homeostasis disrupt this symbiosis and initiate adaptive responses with unpredictable outcomes for the fetus or even the neonate. This may lead to development of pathological phenotypes arising from developmental reprogramming involving interaction of genetic, epigenetic and environmental-driven pathways, sometimes with acute consequences (e.g growth impairment) and sometimes delayed (e.g enhanced susceptibility to disease) that last well into adulthood. Most of these adaptive mechanisms are activated and controlled by hormones of the hypothalamo-pituitary adrenal (HPA) axis under the influence of placental steroid and peptide hormones. In particular, the hypothalamic peptide corticotropin releasing hormone (CRH) plays a key role in feto-maternal communication by orchestrating and integrating a series of neuroendocrine, immune, metabolic and behavioural responses. CRH also regulates neural networks involved in maternal behaviour and this determines efficiency of maternal care and neonate interactions. This review will summarise our current understanding of CRH actions during the perinatal period, focusing on the physiological roles for both mother and offspring and also how external challenges can alter CRH actions and potentially impact on fetus/neonate health.